Effects of linalyl acetate on oxidative stress, inflammation and endothelial dysfunction: can linalyl acetate prevent mild cognitive impairment? - Shin, You Kyoung; Seol, Geun Hee (Frontiers in Pharmacology, 2023)
Mild cognitive impairment (MCI) is a major public health challenge with an increasing prevalence. Although the mechanisms underlying the development of MCI remain unclear, MCI has been reported to be associated with oxidative stress, inflammatory responses, and endothelial dysfunction, suggesting that agents that reduce these factors may be key to preventing MCI. Currently, no agents have been approved for the treatment of MCI, with the efficacy of commonly prescribed cholinesterase inhibitors remaining unclear. Relatively safe natural products that can prevent the development of MCI are of great interest. Linalyl acetate (LA), the major component of clary sage and lavender essential oils, has been shown to have a variety of pharmacological effects, including anti-hypertensive, anti-diabetic, neuroprotective, anti-inflammatory, and antioxidant properties, which may have the potential for the prevention of MCI. The present review briefly summarizes the pathogenesis of MCI related to oxidative stress, inflammatory responses, and endothelial dysfunction as well as the benefits of LA against these MCI-associated factors. The PubMed and Google Scholar databases were used to search the relevant literature. Further clinical research may lead to the development of new strategies for preventing MCI, particularly in high-risk populations with oxidative stress, inflammatory responses, and endothelial dysfunction (e.g., patients with hypertension and/or diabetes mellitus).